PENGARUH PENERAPAN MODEL CONNECTING ORGANIZING REFLECTING EXTENDING (CORE) TERHADAP MINAT BELAJAR DAN PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Rahmat Nugraha; Achmad Mudrikah; Samnur Saputra (Universitas Islam Nusantara, 2022)
This research is based by the low of level of student’s interest in learning and students' critical thinking skills. One alternative can be applied to increase student’s interest in learning and students' critical thinking skills is Connecting Organizing Reflecting Extending (CORE) method. This research aims determine whether there is a positive influence on the Connecting Organizing Reflecting Extending (CORE) method on student’s interest in learning and increase student’s critical thinking skills. The research population was students of class X Muhammadiyah 6 High School in Bandung District. The research sample was Muhammadiyah 6 Kertasari high school students in class X Mipa 1 and X Mipa 2. The research method used was a Quasi experiment with a Non-Equivalent Control Group Design research design. The instruments used are student’s interest questionnaire, students' critical thinking skills test, and ovservation sheet. The data analysis technique uses independent sample T-test and cohen’s d test. The results of the research are: 1) The Connecting Organizing Reflecting Extending (CORE) learning model has a positive effect on student’s interest in learning 2) The Connecting Organizing Reflecting Extending (CORE) model has a positive effect on increasing students' critical thinking skills.